(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Placenta previa refers to placenta which is totally or partly implanted in lower segment of the uterus. Mortality and morbidity of mother increase with placenta previa due to the increase in the incidence of bleeding during pregnancy. This study aims to define placenta previa prevalence among pregnant women at AL-Fallujah teaching hospital and to determine the risk factors and their association with placenta previa incidence in al-Fallujah city population. This retrospective cohort study investigated medical registry of 6339 gravid women in al-Fallujah teaching Hospital in Iraq. We find 13 cases of placenta previa (0.21%) amongst the 6339 cases registered. The risk factors that strongly appeared to affect the complication of pregnancy with placenta previa were; advanced maternal age of ? 35, parity, previous curettage and previous cesarean section (P<0.01). The most important pregnancy outcomes of the placenta previa were lost blood of mother more than five hundred cubic centimeter (P = 0.000) and Apgar score of the baby at first minute equal or less than 7 (P = 0.003), Placenta accretta and cesarean hysterectomy (P< 0.01). These findings are the same as those recorded in other research for Asian, American and European gravid women, with some other detected factors.